Risk Assessment of Flash Flood to Buildings Using an Indicator-Based Methodology: A Case Study of Mountainous Rural Settlements in Southwest China - Zhen, Yiwei; Liu, Shuguang; Zhong, Guihui; Zhou, Zhengzheng; Liang, Jiyu; Zheng, Weiqiang; Fang, Qi (Frontiers in Environmental Science, 2022)
In southwest China, flash floods occur frequently and often cause severe damage to residential building areas, especially in mountainous rural settlements. Risk assessment is crucial in the hazard mitigation policies and measures. However, the study on the quantitative assessment of flash flood risk for buildings is still less explored. In this study, an indicator-based assessment approach is proposed to assess the risk of buildings threatened by flash floods. The flood hazard is first simulated with 1D/2D hydrodynamic model to determine the buildings exposed to the flood and flood inundation indicators. Then, a combination of virtual surveys and building census information is used to collect information on indicators of exposed buildings and their surroundings. The indicator scores are calculated using the building flash flood risk indicator system constructed in this study which includes the flood hazard and building vulnerability indicators. A flood risk index (FRI) combining flood hazard index (FHI) and building vulnerability index (VI) is developed by weighted aggregation of indicators using combination weights calculated by the game theory approach. Based on FRI, the flash flood risk of mountainous buildings is quantitatively assessed. Taken a key mountainous rural settlement in southwest China as an example, the proposed methodological framework enables the quantitative calculation and assessment of the risk of rural buildings to flash flood. The overall framework can provide an applicable approach for flood mitigation decisions in mountainous settlements.